A study on the importance of oral communication skills among administrative support staff at Pahang road transport department, Kuantan / Hasmariza Hasan, Norhafiza Ahmad Azhar and Siti Marsyitah Mat Ali - Hasan, Hasmariza; Ahmad Azhar, Norhafiza; Mat Ali, Siti Marsyitah (2009)
The purpose of this study is to find out whether oral communication skills in face to face, meeting, and formal presentation is effective or ineffective in daily duties among administrative support staff at the Pahang Road Transport Department, Kuantan. The study also can help the administrative support staff to realize the importance of oral communication skills in order to increase their work productivity and then achieve the organization's goals. The scope of the study is to focus on administrative support staff in the public sector at the Pahang Road Transport Department, Kuantan. Other than that, the study use stratified sampling techniques to select a representative from the population. Based on the findings, most of the respondents are aware on the importance of oral communication skills especially in face-to-face communication. However, most of the respondents are rarely involved in meeting and formal presentation because of their position level. For the conclusion, most of the respondents agree that oral communication skills are important in increasing work productivity. Top management commitment, training, and motivation program are the recommendations that are considered most appropriate in order to improve the oral communication skills and increase awareness among the employees. For future research, the study can be extended to other public oriented organization or private sector and the target respondents also can be changed.